99mTc-MIBI Scintigraphy for the Preoperative Assessment of Histological Response to Neoadjuvant Chemotherapy in Patients With Osteosarcoma: A Systematic Review and a Bivariate Meta-Analysis - Wu, Fashuai; Huang, Yu; Huang, Xin; Fang, Silang; Huang, Xiaohui; Huang, Xin; Zhang, Zhicai; Shao, Zengwu (Frontiers in Oncology, 2020)
Purpose: There have been many attempts to preoperatively evaluate the chemotherapy response of osteosarcoma patients using 99mTc-MIBI scintigraphy. However, the evaluations were lack of consistency. We performed this systematic review and meta-analysis to systematically evaluate the ability of 99mTc-MIBI scintigraphy in preoperatively assessing the response of osteosarcoma patients to neoadjuvant chemotherapy. Methods: For this systematic review and meta-analysis, PubMed, Web of Science, OVID, the Cochrane Library and CNKI were searched. Eligible studies were included based on the defined criteria. The index test was 99mTc-MIBI scintigraphy, the reference standard was tumor necrosis rate. Quality Assessment of Diagnostic Accuracy Studies-2 was adopted for quality assessment of included studies. The statistical pooling analysis, meta-regression analysis, subgroup analysis, sensitivity analysis and publication bias of our research were performed using STATA 15. Results: 8 articles with 189 osteosarcoma patients were included in this systematic review and meta-analysis. Our results demonstrated that the threshold effect of our meta-analysis was significant. The uptake change ratio of 99mTc-MIBI scintigraphy had a pooled sensitivity, specificity, positive and negative likelihood ratio, diagnostic odds ratio and the area under curve of 0.98 (0.58-1.00), 0.68 (0.47-0.84), 3.1 (1.7-5.5), 0.03 (0.00-0.90), 103 (4-3003) and 0.91 (0.88-0.93) in preoperative assessment of response of osteosarcoma patients to neoadjuvant chemotherapy. Meta-regression analysis and subgroup analysis indicated the factors of method and cut off value may introduce the heterogeneity. The pooled sensitivity, specificity, positive and negative likelihood ratio, diagnostic odds ratio and the area under curve of washout rate of 99mTc-MIBI were 0.87 (0.69-0.95), 0.91 (0.75-0.97), 9.3 (3.2-27.0), 0.15 (0.06-0.37), 64 (14-301) and 0.89 (0.86-0.92) respectively. Sensitivity analysis and publication bias demonstrated our meta-analysis was of reliability. Conclusion: Both the ΔUR and WR derived from 99mTc-MIBI scintigraphy were valuable in preoperatively assessing the response of osteosarcoma patients to neoadjuvant chemotherapy, and ΔUR may possess a more outstanding diagnostic accuracy than WR.